PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF PADA MATA PELAJARAN DASAR-DASAR PROGRAM KEAHLIAN KELAS X DKV - Rahmatin Anisa; Heri Mulyono; Mourend Devegi (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2023)
The primary objective of this study is to develop interactive learning media for the subject of Basic Expertise in Class X DKV, utilizing the Adobe Animate application. This approach aims to ensure the validity and practicality of its implementation. The research methodology employed is Research and Development (R&D), which follows the ADDIE model encompassing five essential phases: analysis, design, development, implementation, and evaluation.The validation results provided by media experts indicate a percentage of 86.57%, falling within the category of "highly valid." Similarly, the material's validity stands at 93.75%, also classified as "highly valid." The practicality testing for the educational game media, as evaluated by teachers, demonstrates a practicality rate of 97.5%—characterized as "highly practical." In a parallel fashion, student responses reflect a 83.14% score in the "highly practical" category. Derived from the research findings, it can be concluded that the interactive learning media designed for the Basic Expertise Class X DKV exhibit high levels of validity and practicality.